(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the content, importance, and methods of applying a competency-based approach in primary school technology lessons. It analyzes the ways to develop technological knowledge, skills, and abilities in students through modern approaches, interactive methods, and practical tasks based on competencies.